Nutritional, phytochemical, and in vitro anticancer potential of sugar apple (Annona squamosa) fruits - Mohamed Gamal Shehata (Nature Portfolio, 2021)
Abstract In plants, Fruits and their wastes are the main sources of bioactive compounds. Currently, Annona fruits have attracted the attention of people interested in health-promoting foods due to their phytochemical content that their activities were not studied before. This study aimed to explore the potential antioxidant, antimicrobial, and in vitro anticancer activity of two cultivars Annona squamosa (Annona b. and Annona h.) seed, peel, and pulp. We also meausred phenolic, flavonoid, sulfated polysaccharide, tannins, and triterpenoids. Polyphenol identification was determined using RP-HPLC. Results of the antioxidant activity revealed that the highest activity was observed for Annona h. seed extract using DPPH and ABTS assays with IC50 6.07 ± 0.50 and 9.58 ± 0.53 µg/ml, respectively. The antimicrobial activity against various pathogenic strains revealed that the peel extracts of both Annona b. and Annona h. exhibited the best antimicrobial activity. We also assessed the IC50 values for anticancer activity in all six Annona b. and Annona h samples against four cancer cell lines colon (Caco-2), prostate (PC3), liver (HepG-2), and breast (MCF-7) using MTT assay. Annona b. and Annona h seed extracts had the lowest IC50 values for four cancer cell lines with 7.31 ± 0.03 and 15.99 ± 1.25 for PC-3 and MCF-7, respectively. Both seed extracts, Annona b. and Annona h., showed significantly down-regulated mRNA expression of Bcl-2 and up-regulated p53 in all treated cell lines. Apoptosis was evaluated using nuclear staining, flow cytometric analysis, and immunohistochemistry of the proliferation marker (Ki-67). Additional studies are required to characterize the bioactive compounds responsible for the observed activities of Annona seed and determine its mechanism as an anticancer drug.